HUBUNGAN ANTARA PENGETAHUAN DAN DUKUNGAN SUAMI DENGAN INTENSITAS KUNJUNGAN ANTENATAL CARE (ANC) - Astuti, Desti Widya; Puspitasari, Yepiza; Eka Pramanda, Andini (Jurnal Kesehatan dan Pembangunan, 2025)
Antenatal care (ANC) is a government program that aims to prevent the causes of morbidity and mortality in pregnant women and children. The aim of the research is to determine the relationship between husband's knowledge and support and the intensity of antenatal care (ANC) visits at the Independent Midwife Practice (PMB) Irma Suryani, Prabumulih City in 2024. The research method is analytical, using a cross-sectional approach. The population of this study were all birthing mothers who visited PMB Irma Suryani when conducting research from March to April 2024. The sample taken in this study used the Accidental Sampling technique method, namely 43 people. The research instrument is a questionnaire. The results of the research based on bivariate analysis showed that of the 36 respondents with good knowledge, there were 33 respondents (76.7%) who carried out complete antenatal care visits, while of the 7 respondents who had poor knowledge, there were 2 respondents (4.7%) who carried out antenatal care visits. complete. Of the 34 respondents who received husband support, there were 32 respondents (74.4%) who had complete antenatal care visits, while of the 9 respondents who did not receive husband support, there were 3 respondents (7%) who had complete antenatal care visits. Conclusion: There is a significant relationship between knowledge and antenatal care visits with a P value of 0.001 < ? 0.05 and there is a significant relationship between husband's support and antenatal care visits with a P value of 0.000 < ? 0.05.